Tris(4-chlorophenyl) phosphate - Joshua Birch; Eric Cyriel Hosten; Richard Betz (IUCrData)
The title compound, C18H12Cl3O4P, is the symmetric phosphate derived from para-chlorophenol and phosphoric acid. Two of the three aromatic moieties adopt syn-orientation towards the P=O bond while the last chlorophenol ring is pointing away from this bond. In the extended structure, C—H...O bonds connect the individual molecules into sheets lying perpendicular to the crystallographic b axis.